2009
DOI: 10.1007/s00774-008-0026-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the classical NF-κB pathway prevents osteoclast bone-resorbing activity

Abstract: The classical NF-kappaB pathway plays an important role in osteoclast formation and differentiation; however, the role of NF-kappaB in osteoclast bone-resorbing activity is not well understood. To elucidate whether NF-kappaB is important for osteoclast bone-resorbing activity, we used a selective peptide inhibitor of the classical NF-kappaB pathway named the NBD peptide. Osteoclasts were generated using bone marrow macrophages in the presence of M-CSF and RANKL. The NBD peptide dose-dependently blocked the bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…S100A8 was shown to be an endogenous ligand for TLR-4, inducing intracellular translocation of myeloid differentiation factor 88 and activating interleukin-1 receptor-associated kinase and NF-B (12), the latter being crucial for osteoclast differentiation and function (47,48). Using TLR-4-deficient osteoclasts, we clearly demonstrated complete blockade of the S100A8-mediated increase in osteoclast formation and bone resorption.…”
Section: Discussionmentioning
confidence: 82%
“…S100A8 was shown to be an endogenous ligand for TLR-4, inducing intracellular translocation of myeloid differentiation factor 88 and activating interleukin-1 receptor-associated kinase and NF-B (12), the latter being crucial for osteoclast differentiation and function (47,48). Using TLR-4-deficient osteoclasts, we clearly demonstrated complete blockade of the S100A8-mediated increase in osteoclast formation and bone resorption.…”
Section: Discussionmentioning
confidence: 82%
“…(23,54) Recent evidence, however, has shown that suppression of the NF-kB signaling pathway by the NBD peptide was able to prevent the antiosteoblastogenic activity of TNF-a in vitro, (55) suggesting that the NBD peptide could have an effect on bone formation and bone resorption in vivo. In this study, we found that the NBD peptide could prevent and rescue the reduced osteogenesis caused by LPS injection in vivo (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs have been suggested to be involved in the pathogenesis of RA and OA through their ability to degrade proteoglycans [Flannery et al, 1992;Humbry et al, 1995]. NF-κB is essential for osteoclast formation and survival through the receptor activator of the nuclear factor kappa-B ligand (RANKL) pathway [Soysa et al, 2009]. Abnormal activation of NF-κB signalling in osteoclasts has been observed in osteolytic conditions, including arthritis, Paget's disease of bone, and periodontitis [Xu et al, 2009].…”
Section: Nf-κb In Ra Joint Destructionmentioning
confidence: 99%
“…Previous studies have shown that NF-κB controls osteoclast activation through RANKL signalling [Soysa & Alles, 2009], while inhibition or deletion of RANKL prevents bone destruction [Zwerina et al, 2004;Pettit et al, 2001]. The protective effect of MG132 may be a consequence of with interfering osteoclast activation through the RANKL signalling pathway that is under control of NF-κB, or by enhancing the osteoblast activity.…”
Section: Proteasome Inhibition and Joint Destructionmentioning
confidence: 99%